PENGENALAN KOMPUTER DASAR PADA SISWA SD 43 BENGKULU - Keken Pinandita; Marhalim Marhalim; Prans Joya Santana; Rahmat Karindra (Jurnal Pengabdian, 2023)
The priority issue during street vendors is the lack of knowledge of students at SD N 43 in Tanah Patah, Singgaran Jati District, Bengkulu City about software such as Microsoft Word and others. This is due to a lack of technological information available at the SD, therefore In this opportunity for street vendors, I took a step through a work program in the form of an introduction to basic computers and an introduction to software such as Microsoft Word and others for the students of SD N 43 so that they know a little about the technology that exists today besides that they also don't have a PC (Personal). Computer) themselves at home so they don't know the basics of computers and based on the survey that has been carried out there is also a problem that they have never received direct training or guidance about computers. Meanwhile, at this time this is very much needed in education. However, in responding to this I took many steps in the form of introducing Microsoft office word, introducing basic IT, and holding social media outreach properly and correctly to students of SD N 43 in Tanah Patah, Singgaran Jati District, Bengkulu City. with the intention of these children can use it well Â  Â